A sensor for formaldehyde detection: luminescent metal–organic framework [Zn2(H2L)(2, 2′-bpy)2(H2O)]n. Issue 61 (4th July 2015) - Zhao, Zhengyan; Hao, Juanyuan; Song, Xuedan; Ren, Suzhen; Hao, Ce
<x xml:space="preserve">Abstract</x> The comparison between the two systems shows that the encapsulation of formaldehyde can affect the luminescence behavior of [Zn2(H2L)(2, 2′-bpy)2(H2O)]n.